-6(5-x)+1=3(x+2)

Simple and best practice solution for -6(5-x)+1=3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(5-x)+1=3(x+2) equation:


Simplifying
-6(5 + -1x) + 1 = 3(x + 2)
(5 * -6 + -1x * -6) + 1 = 3(x + 2)
(-30 + 6x) + 1 = 3(x + 2)

Reorder the terms:
-30 + 1 + 6x = 3(x + 2)

Combine like terms: -30 + 1 = -29
-29 + 6x = 3(x + 2)

Reorder the terms:
-29 + 6x = 3(2 + x)
-29 + 6x = (2 * 3 + x * 3)
-29 + 6x = (6 + 3x)

Solving
-29 + 6x = 6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-29 + 6x + -3x = 6 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-29 + 3x = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-29 + 3x = 6 + 0
-29 + 3x = 6

Add '29' to each side of the equation.
-29 + 29 + 3x = 6 + 29

Combine like terms: -29 + 29 = 0
0 + 3x = 6 + 29
3x = 6 + 29

Combine like terms: 6 + 29 = 35
3x = 35

Divide each side by '3'.
x = 11.66666667

Simplifying
x = 11.66666667

See similar equations:

| 11x-3=5x+21 | | 0.16-0.01(x+2)=0.03(2-x) | | 4(n-12)=12(n-4) | | 125+m=725 | | 35=-2x-25 | | 4(n-12)=12(4-n) | | -4/5=-1/4-5/6q | | (9x-4)(5x+5)= | | X^2-8=9x | | -7(-4-4x)-6=1+7x | | 3(x-7)-4(2+x)=3 | | -5qx+6qx(5x-6)-65qx=-66 | | f(-3)=15(-3)+4 | | v-2+5= | | 4(12-n)=12(n-4) | | 5x+3=-77 | | 2x+40+3x+20=180 | | 2x=1.67 | | -3y+8(1y+3)=7+9(-3-y) | | 42=8m+133333 | | t+1+-4t+8=21 | | 4LW=V | | 12+x=6.8 | | t+1-4t+8=22 | | 12+x=16.8 | | -5(-4x-10)=-70 | | 4x^3-16x^2+13x=0 | | x^3-16x^2+13x=0 | | 5x-2+4x+2=-18 | | 1y=2x-4 | | 2(6t-4)=22t-t+4 | | 10=4x^2-2x+8 |

Equations solver categories